Nutritional Management of the Critically Ill Neonate: A Position Paper of the ESPGHAN Committee on Nutrition. Issue 2 (August 2021) - Moltu, Sissel Jennifer; Bronsky, Jiri; Embleton, Nicholas; Gerasimidis, Konstantinos; Indrio, Flavia; Köglmeier, Jutta; de Koning, Barbara; Lapillonne, Alexandre; Norsa, Lorenzo; Verduci, Elvira; Domellöf, Magnus
ABSTRACT: Objectives: The nutritional management of critically ill term neonates and preterm infants varies widely, and controversies exist in regard to when to initiate nutrition, mode of feeding, energy requirements, and composition of enteral and parenteral feeds. Recommendations for nutritional support in critical illness are needed. Methods: The ESPGHAN Committee on Nutrition (ESPGHAN-CoN) conducted a systematic literature search on nutritional support in critically ill neonates, including studies on basic metabolism. The Medline database and the Cochrane Library were used in the search for relevant publications. The quality of evidence was reviewed and discussed before voting on recommendations, and a consensus of 90% or more was required for the final approval. Important research gaps were also identified. Results: This position paper provides clinical recommendations on nutritional support during different phases of critical illness in preterm and term neonates based on available literature and expert opinion. Conclusion: Basic research along with adequately powered trials are urgently needed to resolve key uncertainties on metabolism and nutrient requirements in this heterogeneous patient population.